2022
DOI: 10.2147/vhrm.s382726
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for and Treatment of Chronic Venous Disease in Thai Patients

Abstract: Introduction The prevalence of chronic venous disease (CVD), a common health care problem, is still underestimated. A few previous epidemiologic studies have report Asian patients with this condition in western countries, but not in Asian countries. The aim of this study was to determine risk factors for CVD and its treatment in Thai individuals. Methods In this cross-sectional study, we collected data of patients with CVD visiting Chulabhorn Hospital Vascular Clinic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…CVI was found to be more prevalent in obese people in industrial countries and after long‐term standing posture. Taengsakul (2022) has shown that in the Tai population, the BMI of patients with severe CVI was significantly higher compared to patients suffering from mild‐to‐moderate CVI 4 . The severity of CVI increases with age, affecting the female population more often 2 .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…CVI was found to be more prevalent in obese people in industrial countries and after long‐term standing posture. Taengsakul (2022) has shown that in the Tai population, the BMI of patients with severe CVI was significantly higher compared to patients suffering from mild‐to‐moderate CVI 4 . The severity of CVI increases with age, affecting the female population more often 2 .…”
Section: Introductionmentioning
confidence: 99%
“…1 The development of CVI likely has several contributory factors, including a hereditary component and many risk factors (Table 1 ). 2 , 3 , 4 , 5 Venous dysfunction originates from venous hypertension and is associated with venous reflux due to poorly functioning or incompetent venous valves, which ultimately reduces venous return, leading to blood pooling, hypoxia, and inflammation. 6 Valvular injury in the vein or vein occlusion occurs as well.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study reporting the incidence of chronic wounds from a nationwide database in Singapore, the Indian minority had a higher incidence rate of venous wounds compared to the Chinese majority, especially among those aged 50 years and above 9 . Prevalence in other south-east Asian countries is unreported 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Chronic venous disease (CVD) is a frequent pathology and a common health care problem. The prevalence of this condition remains underestimated, early evidence of CVD being frequently overlooked by general practitioners [ 1 ]. Clinical manifestations of CVD can range from mild to severe, such as telangiectasia, varicose veins (most notably), lipodermatosclerosis or venous ulceration, and pain is one of the most common symptoms [ 2 , 3 ].…”
Section: Introductionmentioning
confidence: 99%